(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Intestinal malrotation is a rare congenital disease due to abnormal intestinal rotation and fixation of the intestinal tract in the early embryonic state. Adult cases are very rare. Midgut malrotation typically presented during the first few months of life but may sometimes appear later in life, causing difficulties and mistakes in diagnosis. An unusual presentation of this condition has led to diagnostic dilemma. Diagnosis is delayed because respective symptoms were not adequately considered in adults. We present a case report of 35 years old Muslim male presented with history of gradually increasing vague abdominal pain at upper and mid abdomen for 5 months with history of vomiting after heavy meal. On examination we found that patient was anxious and ill looking, Body stature average but patient was malnourished and dehydrated. Mild tender epigastric region. No palpable lump. No organomegaly. Succussion splash absent. Endoscopy of upper GIT was normal and full colonoscopy found also normal. Barium follow through x-ray revealed stricture at 3rd part of Duodenum with malrotation of gut. Open Ladd procedure with gastrojejunostomy under G/A was performed. J. Dhaka National Med. Coll. Hos. 2024; 30 (01): 42-46